Graft Pre-conditioning by Peri-Operative Perfusion of Kidney Allografts With Rabbit Anti-human T-lymphocyte Globulin Results in Improved Kidney Graft Function in the Early Post-transplantation Period—a Prospective, Randomized Placebo-Controlled Trial - Ritschl, Paul V.; Günther, Julia; Hofhansel, Lena; Kühl, Anja A.; Sattler, Arne; Ernst, Stefanie; Friedersdorff, Frank; Ebner, Susanne; Weiss, Sascha; Bösmüller, Claudia; Weissenbacher, Annemarie; Oberhuber, Rupert; et al. (Frontiers in Immunology, 2018)
Introduction: Although prone to a higher degree of ischemia reperfusion injury (IRI), the use of extended criteria donor (ECD) organs has become reality in transplantation. We therefore postulated that peri-operative perfusion of renal transplants with anti-human T-lymphocyte globulin (ATLG) ameliorates IRI and results in improved graft function. Methods: We performed a randomized, single-blinded, placebo-controlled trial involving 50 kidneys (KTx). Prior to implantation organs were perfused and incubated with ATLG (AP) (n=24 kidney). Control organs (CP) were perfused with saline only (n=26 kidney). Primary endpoint was defined as graft function reflected by serum creatinine at day 7 post transplantation (post-tx). Results: AP-KTx recipients illustrated significantly better graft function at day 7 post-tx as reflected by lower creatinine levels, whereas no treatment effect was observed after 12 months surveillance. During the early hospitalization phase, 16 of the 26 CP-KTx patients required dialysis during the first seven days post-tx, whereas only 10 of the 24 AP-KTx patients underwent dialysis. No treatment-specific differences were detected for various lymphocytes subsets in the peripheral blood of patients. Additionally, mRNA analysis of zero-hour biopsies post incubation with ATLG revealed no changes of intragraft inflammatory expression patterns between AP and CP organs. Conclusion: We here present the first clinical study on peri-operative organ perfusion with ATLG illustrating improved graft function in the early period post kidney transplantation. (ClinicalTrials.gov: NCT03377283; https://clinicaltrials.gov/ct2/show/NCT03377283)